2005
DOI: 10.1271/bbb.69.1568
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification, and Structure of a Potent Alkyl-Peroxyl Radical Scavenger in Crude Canola Oil, Canolol

Abstract: Alkylhydroperoxides in oxidized oil are undesirable components because they become alkylperoxyl radicals (ROO*) in the presence of heme, hemoglobin, or myoglobin in red meat. ROO* are biochemically reactive and damage nucleic acids and proteins, thereby harming living cells. We isolated a component, a highly potent ROO* scavenger, from crude canola oil (rapeseed), which we designated canolol, and identified its chemical structure, 4-vinyl-2,6-dimethoxyphenol. The canolol content of crude canola oil greatly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 1 publication
12
129
1
Order By: Relevance
“…They have also shown that there is a synergistic effect between the different phenolic compounds in rapeseed oil. Such an effect is also confirmed by Wakamatsu et al (2005) and by Spielmeyer et al (2009), who reported no loss of tocopherols during the thermal processing of seeds and explained this as being due to the protective activity of canolol. Moltke-Sørensen et al (2013) showed the high antioxidant activity of canolol in an oil-water emulsion, which in comparison to other compounds is ordered as follows: BHT > canolol > sinapine > canola extract > sinapic acid.…”
Section: Antioxidant Activitysupporting
confidence: 66%
See 3 more Smart Citations
“…They have also shown that there is a synergistic effect between the different phenolic compounds in rapeseed oil. Such an effect is also confirmed by Wakamatsu et al (2005) and by Spielmeyer et al (2009), who reported no loss of tocopherols during the thermal processing of seeds and explained this as being due to the protective activity of canolol. Moltke-Sørensen et al (2013) showed the high antioxidant activity of canolol in an oil-water emulsion, which in comparison to other compounds is ordered as follows: BHT > canolol > sinapine > canola extract > sinapic acid.…”
Section: Antioxidant Activitysupporting
confidence: 66%
“…In studies examining the levels of tocopherols in rapeseed oil produced from roasted seeds, some authors observed an increase in the amounts of particular tocopherols and plastochromanol-8 (Siger et al, 2015;Shrestha and De Meulenaer, 2014). Neither Wakamatsu et al (2005) nor Spielmeyer et al (2009) found any significant differences in the tocopherol content of canola oil from unroasted and roasted raw material. The lack of a decrease in tocopherol levels under the influence of high-temperature roasting of the rapeseed is often explained by the synergistic interaction of phenolic compounds (here, mainly canolol) -the amount of which increases in proportion to the temperature and roasting duration (Matthäus, 2013a;Siger et al, 2015).…”
Section: Tocochromanol Contentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Soybean oil and olive oil had mild effects on myocardial structure (Aguila et al, 2004). Recently, a potent antioxidant named canolol was isolated from crude canola oil and its potency was found to be greater than that of some well-known antioxidants, including a-tocopherol, vitamin C and quercetin (Wakamatsu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%